An Analysis of Students' Scientific Attitude towards Biology Practice at MAN 1 Situbondo - Arofah, Dian Nuril; Sihabuddin, Mochamad Adzani; Ubaidillah, A. Yusril; Dhona, Lawdy Rahma (Aspirasi Masyarakat Intelektual Islam Nusantara, 2022)
This research aims to investigate the scientific attitude of MAN 1 Situbondo students regarding the biology topic practicum. During the odd semester of 2021/2022, numerous class XII students from the Mathematics and Natural Sciences Department of MAN 1 Situbondo conducted this study. This study's participants were class 12 students at MAN 1 Situbondo. This study is a descriptive quantitative study. Online data collecting on the scientific attitudes of students is conducted by filling out a Google form, using a questionnaire approach or completing a questionnaire. Curiosity, honesty, responsibility, confidence, collaboration, and openness are facets of the scientific mindset utilized in data collecting. The results indicated that the curiosity value of the scientific attitude was 81.3% in the very good category, 71.9% in the good category for honesty, 84.4% in the very good category for responsibility, 81.3% with the good category for openness, 96.9% with the very good category for confidence, and 100% with the very good category for cooperation. Overall, 85.9% of students' scientific attitudes during practical activities in general biology courses were rated as very excellent.